Euro-Mediterranean Journal for Environmental Integration - Euro-Mediterranean Journal for Environmental Integration (Springer Nature, 2026)
Euro-Mediterranean Journal for Environmental Integration is a scientific forum promoting original research and reviews on all areas of environmental sciences.
FI 0.32
Q3
Keywords: Earth; Space & Environmental Sciences; Environmental Geoscience; Geociencia; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Sostenibilidad; Mediterráneo; Biorremediación; Ecotoxicología; Energía renovable; Riesgos geológicos; Teledetección